Facile synthesis of high-purity single-twinned Au nanocrystals through manipulation of reaction kinetics1. Issue 35 (21st September 2015) - Wang, Yi; Fu, Wensheng; Hu, Xue
<x xml:space="preserve">Abstract</x> Single-twinned truncated Au right bipyramids with shape purity >90% and sizes controlled between 15 and 50 nm have been fabricated for the first time. The success of our synthesis relies on the use of an appropriate precursor to manipulate the reaction kinetics.